Ageism: Does it Exist Among Children?. (2007) - Davidovic, Mladen; Djordjevic, Zorana; Erceg, Predrag; Despotovic, Nebojsa; Milosevic, Dragoslav P.
Abstract : Ageism is stereotyping and prejudice against individuals or groups because of their age. Robert Butler first used it in 1969, to express a systematic stereotyping and discrimination against elderly people. Available data appears to confirm that attitudes of children to the old age differ from that of adults. The study population consisted of 162 subjects (56 school children, 48 nurses and 58 elderly patients). Each subject in the survey was asked to respond to the following three questions: Question #1: "Is the old age unattractive ?"; Question #2: "How old is an old man? Question #3: "What should you do to have a long life (what is good for longevity)? The majority of polled children (33) gave positive statements about ageing in their responses to the first item, while most of the nurses gave condition answers, like: "It is not unattractive if you are healthy". Elderly subjects made up a group with the majority of negative responses (in percentage), as only 33% of them answered that old age is not unattractive. All three groups of subjects demonstrated a good knowledge of what is considered good for longevity, and had a generally positive health attitude. Our results indicate that majority of children have positive perception and attitude about old age, which leads us to conclusion that ageism is adopted later in life.